The Masipag-Farming Experience among marginal upland farmers in Barangay Carit-an, Patnongon, Antique. - Ledason, Roger S.
This paper presents a case study of marginal upland farmers in barangay Caritan, patnongon, Antique which assesses the impact of the Masipag Program and emphasizes the factors that are related to the acceptance or rejection of an agricultural innovation, the Masipag Technology implemented by Hantique Igcabuhi center - Hublag Evelio (HIC-HE) under its food production and environment education program (FPEEP) that focuses on sustainable agriculture by improving the capabilities of target communities to manage appropriately their diminishing natural resources as the key to sustainable development. The first of this program started in Antique on March 1995 through Carit-an Upland Farmers Association (CUFA) with Antique Integrated Area Development (ANIAD) as the funding agency. The findings of this study will be used to determine if the Masipag Technology is worth expanding and is effective for the call of sustainable development. Ocular observation was made through farm visits. The impression were validated during individual farmer interviews and group discussions. Four farmers selected randomly among Masipag Technology adoptor for case studies. Fourteen farmers of the twenty four members of CUFA under the programme were selected as respondents. Survey and ocular observations was done from January to February 1998. Results of the in depth interviews/case studies have positive impact exerted both on the farmer's lives as well as those of their families and likewise on farm environment which put an end to ecological destruction. Results shows that three of the respondents claimed that there was minimal impact for reasons that there have no significant changes in their needs, work loads and economic status because of lack of tenurial security wherein still the land owner's decision must be followed, thus the incentive to produce more and to spend more time and effort to make his land more productive will not be fulfilled. further, two of the respondents who answered that there was no changes effected by the program with reasons of wait and see attitude and the belief of more laborious in farm maintenance with decreased productivity. Furthermore, majority of the farmer respondents assured on the positive benefits from the technology. These positive benefits include economic, environmental and social aspects. Meanwhile, the acceptance of new innovation, the Masipag Technology depends upon different factors such as educational, economic, political and social factors, felt needs, aspirations, work concepts, interest, physical capability and relationship factors between the innovators and the farmers. Among the successful farmers, the innovative potential was comparatively higher owing to the presence of a felt need or desire to improve their status in life, interest, physical capability, high literacy rate, and close relationships between the farmers and the innovators. Likewise, farmers with security of tenure over the land they till or owner/cultivator have high innovative potential compared to farmers with lack of security of tenure. Hence, security of tenure over the land may help to develop the farmer as a producer and a consumer, if his income rises. It leads to an improved quality of rural life, thus, reduce migration to urban centers and other countries. A spirit of cooperation seemed to have pervaded marginal farmers in the area. This was evident in the utilization of the traditional bayanihan in the program operations. The harmonious relationship existing among farmers was a product of community organizing techniques adopted for the program. These appeared to be very strong partnership among the marginal upland farmers, the HIC-HE staff, and the agricultural technicians of the leading agencies. The absence of effective linkages between the GO, PO and NGO could threaten the sustainability of program implementation. Thus, a tri-partite partnership were very crucial to the sustainability of the program.